VIOLENCE AGAINST AFRICAN-AMERICAN SLAVES AS SEEN IN SOLOMON NOTHUP'S TWELVE YEARS A SLAVE - Maria Manikome; Paula A. Rombepajung; Imelda S. Lolowang (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The purpose of this study was to reveal about violence against African-American slaves; the kinds of violence and impacts of violence to the slaves in Solomon Northup’s Twelve Years a Slave. This study is classified as a qualitative research because the writers gathered the data in the form of words as well as quotation from the work itself. The writers collected the data from two kinds of sources, namely primary source and secondary source. The primary source was taken from the novel Twelve Years a Slave by Solomon Northup, and the secondary sources are the other material that supports the research such as books, articles and websites. This study used a Sociological approach which regards the literary work as a social document that reflects the situation when the literary work was created. The results of this study showed that there are two kinds of violence against African-American slaves in Northup’s work; physical violence and psychological violence. The acts of violence wasreceived by the slaves result in some impacts include physical impact such as, suffering in pain, injury, and sick; and psychological impact such as, fear, trauma, and depression. Through sociological approach, it can be concluded that the novel Twelve Years a Slave really explained the real social condition of African-American slaves that occurred in the 19th century, where they experienced acts of violence from their white masters during slavery.